Museums after modernism : strategies of engagement - Pollock, Griselda (Malden, MA : Blackwell, 2007)
- Un-framing the modern : critical space/public possibility / Griselda Pollock##- Women's Rembrandt / Mieke Bal##- Museums and the native voice / Gerald McMaster##- Exhibiting Africa after modernism : globalization, pluralism and persistent paradigms of art and artifact / Ruth B. Phillips##- Mirroring evil, evil mirrored : timing, trauma and temporary exhibitions / Reesa Greenberg##- A place for uncertainty : towards a new kind of museum / Vera Frenkel##- The ballad of Kastriot Rexhepi : notes on gesture, medium and mediation / Mary Kelly##- Riksutställningar : Swedish traveling exhibitions / Ulla Arnell##- Reframing participation in the museum : a syncopated discussion / Janna Graham, Shadya Yasin##- "There is no such thing as a visitor" / Judith Mastai##- "Anxious dust" : history and repression in the archives of Mary Kelly / Judith Mastai##- On discourse as monument : institutional spaces and feminist problematics / Juli Carson.
CCS Gent
Includes bibliographical references (p. [225]-234) and index.
boek